CRISPR-Cas: A continuously evolving technology - KUMARI, SARITA; SINGH, SUMEET KUMAR; SHARMA, VINAY KUMAR; KUMAR, RAJESH; MATHUR, MANAS; UPADHYAY, TARUN KUMAR; PRAJAPAT, RAKESH KUMAR (The Indian Journal of Agricultural Sciences, 2021)
The discovery of the CRISPR/Cas microbial adaptive immune system and its ongoing development as a genome editing tool represents the work of many scientists around the world. The time line of CRISPR/Cas system shows that this technology is improving continuously to remove the demerits of preceding one with the aim of development of highly efficient, specific with low off target effect and ultimately transgene free technology in light of ethical and environmental issues related with transgenic technology. Initially, CRISPR/Cas9 was developed as method of choice as it provides targeted mutagenesis under in vivo condition and all the homeoalleles of a gene can be targeted in same plant, especially in case of polyploid species efficiently which is difficult through other existing technology. No residual or foreign gene insertion is required and modification is permanent. Now, CRISPR/Cpf1 has been developed as more potent, efficient and simpler than CRISPR/Cas9. Different forms of Cas enzymes provide new avenues for regulation of genomic component. In view of the present devastating COVID-19 disaster the scientists used this novel technology for detection of virus in humans at an early stage of infection thus saving human lives. The evolution of CRISPR/Cas technology, their advantages, apprehensions and solution, experimental design and updates of this technology is discussed in the present review.